Efficacy of novel allogeneic cancer cells vaccine to treat colorectal cancer - Alzeeb, George; Tortorelli, Corinne; Taleb, Jaqueline; De Luca, Fanny; Berge, Benoit; Bardet, Chloé; Limagne, Emeric; Brun, Marion; Chalus, Lionel; Pinteur, Benoit; Bravetti, Paul; Gongora, Céline; et al. (Frontiers in Oncology, 2024)
Colorectal cancer (CRC) remains a significant global health burden, emphasizing the need for innovative treatment strategies. 95 % of the CRC population are microsatellite stable (MSS), insensitive to classical immunotherapies such as anti-PD-1; on the other hand, responders can become resistant and relapse. Recently, the use of cancer vaccines enhanced the immune response against tumor cells. In this context, we developed a therapeutic vaccine based on Stimulated Tumor Cells (STC) platform technology. This vaccine is composed of selected tumor cell lines stressed and haptenated in vitro to generate a factory of immunogenic cancer-related antigens validated by a proteomic cross analysis with patient's biopsies. This technology allows a multi-specific education of the immune system to target tumor cells harboring resistant clones.Here, we report safety and antitumor efficacy of the murine version of the STC vaccine on CT26 BALB/c CRC syngeneic murine models. We showed that one cell line (1CL)-based STC vaccine suppressed tumor growth and extended survival. In addition, three cell lines (3CL)-based STC vaccine significantly improves these parameters by presenting additional tumor-related antigens inducing a multi-specific anti-tumor immune response. Furthermore, proteomic analyses validated that the 3CL-based STC vaccine represents a wider quality range of tumor-related proteins than the 1CL-based STC vaccine covering key categories of tumor antigens related to tumor plasticity and treatment resistance. We also evaluated the efficacy of STC vaccine in an MC38 anti-PD-1 resistant syngeneic murine model. Vaccination with the 3CL-based STC vaccine significantly improved survival and showed a confirmed complete response with an antitumor activity carried by the increase of CD8+ lymphocyte T cells and M1 macrophage infiltration.These results demonstrate the potential of this technology to produce human vaccines for the treatment of patients with CRC.